Bifurcation of periodic solutions of the Navier-Stokes equations in a thin domain - Johnson, Russell; Nistri, Paolo; Kamenskiĭ, Mikhail I. (Topological Methods in Nonlinear Analysis, 1999)
Aim of this paper is to provide conditions in order to guaranteethat the periodic solutions in time and in the space variablesof the Navier-Stokes equations bifurcate.Specifically, we study this problem when the considered state domainhas one dimension which is small with respect to the others which we let to tendto zero. The thinness of the domain represents the bifurcation parameterin our situation.